Synthesis of isopropyldichlorosilane by direct process - Lim, Weon Cheol; Cho, Joo Hyun; Han, Joon Soo; Yoo, Bok Ryul (WILEY-V C H VERLAG GMBH, 2007)
Direct reaction of elemental silicon with a gaseous mixture of isopropyl chloride (1) and hydrogen chloride in the presence of copper catalyst using a stirred bed reactor equipped with a spiral band agitator gave isopropyldichlorosilane having a Si-H bond (2a) as a major product and isopropyltrichlorosilane (2b) along with chlorosilanes, trichlorosilane and tetrachlorosilane. A process for production of 2a was maximized using the 1:0.5 mole ratio of I to HCl and smaller size of elemental silicon at a reaction temperature of 220 degrees C. When a reaction was carried out by feeding a gaseous mixture of 1 [12.9 g/h (0.164 mol/h)] and HCl [2.98 g/h (0.082 mol/h)] to a contact mixture of elemental silicon (360 g) and copper (40 g) under the optimum condition for 45 h, 2a among volatile products kept up about 82 mol % until 35 It and then slowly decreased down 68 mol % in 45 h reaction. Finally 2a was obtained in 38% isolated yield (based on 1 used) with an 85% consumption of elemental silicon in a 45 h reaction. In addition to 2a, 2b was obtained as minor product along with chlorosilanes, trichlorosilane, and tetrachlorosilane. The decomposition of I was suppressed and the production of 2a improved by adding HCl to 1.
Keywords: HYDROGEN-CHLORIDE